2014
DOI: 10.1186/1479-5876-12-149
|View full text |Cite
|
Sign up to set email alerts
|

Implications of differences in expression of sarcosine metabolism-related proteins according to the molecular subtype of breast cancer

Abstract: BackgroundThe goal of this study was to investigate the expression of sarcosine metabolism-related proteins, namely glycine N-methyltransferase (GNMT), sarcosine dehydrogenase (SARDH), and l-pipecolic acid oxidase (PIPOX), in the different breast cancer subtypes and to assess the implications of differences in expression pattern according to subtype.MethodsWe analyzed the expression of GNMT, SARDH, and PIPOX in a tissue microarray of 721 breast cancer cases using immunohistochemistry (IHC). We classified breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…As it was evidenced, sarcosine increased amount also stimulates the SARDH expression. Although there is a lack of direct evidence of linkage between SARDH and PCa aggressiveness, Yoon and coworkers demonstrated that the expression of SARDH is associated with shorter overall survival of subjects suffering from luminal A type breast cancer [25]. Although here we report obvious effects of sarcosine treatment on its pathway in vivo , further analysis of metabolic activities of sarcosine associated enzymes might be done to shed more light into this phenomenon.…”
Section: Discussionmentioning
confidence: 61%
“…As it was evidenced, sarcosine increased amount also stimulates the SARDH expression. Although there is a lack of direct evidence of linkage between SARDH and PCa aggressiveness, Yoon and coworkers demonstrated that the expression of SARDH is associated with shorter overall survival of subjects suffering from luminal A type breast cancer [25]. Although here we report obvious effects of sarcosine treatment on its pathway in vivo , further analysis of metabolic activities of sarcosine associated enzymes might be done to shed more light into this phenomenon.…”
Section: Discussionmentioning
confidence: 61%
“…Although sarcosine is mainly known as a prostate cancer‐associated metabolite, it has also been implicated in a subset of metastatic breast cancer cases. High expression of GNMT and low expression of SARDH, collectively referred to as ‘high sarcosine type,’ is associated with the human epidermal growth factor receptor 2 positive subtype of breast cancer and negatively correlated with disease‐free survival of breast cancer patients . Sarcosine metabolism in breast cancer also appears to be differentially regulated according to the metastatic site, with bone and lung metastases tending to show a ‘high sarcosine type.’ Although information on the importance of sarcosine in other cancer types is currently scarce, it has been shown to play a role in metastatic prostate and breast cancers, the two cancer types with second‐highest incidence rates in men and women, respectively.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Metabolomic analyses indicate that androgen supplementation results in elevated amino acid metabolism and increased methylation activity in PCa cells [114,115]. Interestingly, in breast cancer, the expression of sarcosine-related enzymes has been shown to vary according to cancer subtype [115]. A parallel with GNMT could be established with studies conducted on Nicotinamide N -methyltransferase (NNMT) [116].…”
Section: Androgen Signaling Regulates the Expression Of Enzymes Inmentioning
confidence: 99%